Preserving Faith and Tradition: The Role of Traditional Leaders and Mosques in the Socio-Religious Life of Coastal Communities - Husnul Qodim (Khazanah Sosial, 2023)
This research study investigates the crucial role played by traditional leaders and local mosques in preserving religious and cultural values in the Eretan Wetan coastal community in Indramayu, West Java. Utilizing a sociological approach and observational and interview-based data collection techniques, the study found that Eretan Wetan is a highly religious community where religious and cultural values influence and strengthen each other, despite the disruptions caused by modernity. The mosque serves as a center for both ritual worship and community empowerment, and traditional clerics resist modernity. The research highlights the importance of preserving coastal communities' religious and cultural values and recognizing the roles of traditional leaders and mosques in their socio-religious life. This study is expected to provide input and recommendations for policymakers in developing coastal communities sustainably while preserving their religious and cultural values.